Pengaruh Media Buku Cerita Bergambar Terhadap Pemahaman Membaca Bahasa Mandarin Murid SD kelas 1 W.R. Supratman 2 Medan - Lyna, Lyna; Charissa, Charissa (Journal of Language, Literature and Teaching, 2019)
This research was aimed at finding out the effect of storybook as the learning media on the first grade primary school students’ reading comprehension at W.R. Supratman 2 Medan. The storybook included the interrelated pictures and sentences that formed a coherent story. This research used experimental design. The subjects of this research was 88 students which were divided into 44 students in control group and 44 students in experimental group. From the data analysis, this research revealed that the average score of experimental group was 69.32 which was higher than the average score of control group 48.18 (69.32 bigger 48.18), and the result of t-test showed that tcount = 3.14 was higher than ttabel = 1.68 (3.14 bigger 1.68). It showed that thye effect of the storybook significantly influenced the achievement of the students’ reading comprehension.